Nonpredominant lepidic pattern correlates with better outcome in invasive lung adenocarcinoma. Issue 3 (December 2015) - Mäkinen, Johanna M.; Laitakari, Kirsi; Johnson, Shirley; Mäkitaro, Riitta; Bloigu, Risto; Lappi-Blanco, Elisa; Kaarteenaho, Riitta
Highlights: A series of 112 patients with surgically operated lung adenocarcinoma was reviewed. Histologic subtyping was performed according to the IASLC/ATS/ERS classification. Nonpredominant lepidic pattern was associated with a more favorable prognosis. Correlation was observed between histology, gender and smoking history. Assessment of tumor heterogeneity is essential in the lung adenocarcinoma diagnostics. Abstract: Objectives: Histologic heterogeneity is a typical feature of pulmonary adenocarcinoma. This study aimed to deconstruct the intratumoral growth pattern composition and to examine the prognostic relevance of the current lung adenocarcinoma classification in a series of Finnish lung cancer patients. Materials and methods: A cohort of 112 patients with surgically operated stage I–IV lung adenocarcinoma was retrospectively reviewed. Histologic subtyping was performed according to the classification system established by the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society (IASLC/ATS/ERS). Systematically collected clinical information including survival data was correlated with the subtype status. In addition, emphasis was placed on the nonpredominant histologic patterns, gender and smoking history. Results: The most common subtype was acinar predominant adenocarcinoma with 56 cases (50%). Most tumors were composed of a mixture of two or more growth patterns, and single pattern tumors were rare (9.8%). Micropapillary predominant adenocarcinoma and solid predominant adenocarcinoma were the subtypes with the lowest disease-specific survival rates (5-year DSS 21.4% and 30.4%; shared mean DSS 46.3 months, p  = 0.040). A nonpredominant lepidic component was observed in 24 (21.4%) tumors, and its presence predicted a better outcome (mean DSS 127.4 months vs. 55.7 months, p  = 0.001). This association was confirmed by multivariate analysis ( p  = 0.004). Solid pattern and solid, papillary, micropapillary and cribriform predominant histology associated with smoking ( p  < 0.001), while mucinous pattern was more common in nonsmokers ( p  < 0.001) and in women ( p  = 0.050). Conclusions: Micropapillary and solid predominant adenocarcinomas showed significantly lower survival rate than other major subtypes, yet the prognostic value of the current lung adenocarcinoma classification is not limited only to the predominant growth patterns. The more favorable outcome associated with the nonpredominant lepidic pattern further emphasizes the importance of histologic subtyping and assessment of tumor heterogeneity in the diagnostics of lung adenocarcinoma.